BRONCHIECTASIS IN A PATIENT WHO INHALED A FOREIGN BODY (CASE STUDY) - Stojkovikj, Jagoda; Arbutina, Suzana; Zejnel, Sead; Ismaili, Irfan; Omerova, Berna; Bozinova, Katerina; Hristova, Emilija (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Foreign body aspiration is a life-threatening condition that must be treated immediately. It can be peanuts, nuts, plastic, hairpins, needles, pieces of bone, teeth, dental fillings, etc. Incidents most often occur in children, especially under 3 years of age, but also in adults. Clinical manifestations can vary from mild to severe. Treatment includes bronchoscopy, VATS, and thoracotomy. Thoracoscopy-assisted surgeries can reduce postoperative morbidity, pain, and length of hospitalization. It is known that the long-term presence of a foreign body in the bronchial tree not only results in inflammation, but also causes complications such as bronchiectasis, hemoptysis, and empyema. In our case, we are talking about a young patient aged 32, who was hospitalized at the University Hospital for Pulmonology and Allergology due to a frequent lower respiratory infections and productive cough in the last 5 years. On several occasions she was treated with antibiotic therapy, but without improvement.On the current hospitalization she was treated with double antibiotic therapy and the cough subsided. Later CT scan of the lugs was performed and a foreign body was clearly visualized. She was scheduled for bronchoscopy and extraction of the foreign body. The intervention was successful and our patient isin good condition. Keywords: cough, foreign body, bronchiectasis, bronchoscopy